2014
DOI: 10.1080/21642850.2013.878659
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse prevention in Cape Town's peri-urban settlements: local health trainers' perspectives

Abstract: South Africa currently experiences high levels of alcohol and other drug (AOD) abuse. As a result there is a need for the initiation of regional AOD abuse prevention programmes with a specific focus on youth prevention strategies. The Medical Knowledge Institute (MKI) is a non-profit organisation which develops and facilitates health information workshops to members of disadvantaged peri-urban communities in South Africa. This research investigated the views of eight local MKI health trainers on factors contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…It may be beneficial to routinely screen for problem substance use among self-harm patients and to offer referrals to appropriate substance use treatment centers or, where appropriate, to deliver brief targeted interventions as part of the management of self-harm at the hospital. This is particularly important in SA where there are high rates of substance use and problematic patterns of alcohol use [18, 22]. The lack of accessible, affordable and effective treatments for substance use problems in SA [35] is a significant barrier to suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be beneficial to routinely screen for problem substance use among self-harm patients and to offer referrals to appropriate substance use treatment centers or, where appropriate, to deliver brief targeted interventions as part of the management of self-harm at the hospital. This is particularly important in SA where there are high rates of substance use and problematic patterns of alcohol use [18, 22]. The lack of accessible, affordable and effective treatments for substance use problems in SA [35] is a significant barrier to suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol is the most common substance used in SA [18]. Widespread unrecorded alcohol production (e.g., home-brewing of beer) and illegal selling of alcohol, make it difficult to accurately estimate alcohol consumption in SA [19].…”
Section: Introductionmentioning
confidence: 99%
“…Today, South Africa has the highest rate of alcohol consumption in the southern African region [7,8]. About a third of adults report harmful use [6,[8][9][10]. Alcohol abuse in adolescents is associated with risky sexual behaviours, academic failure, absenteeism, and increased risk of drug use [8].…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas of KwaZulu Natal and Mpumalanga, our findings demonstrate that females who left school for the same reason (not having enough money for school fees) as their rural counterparts were less likely to consume higher amounts of alcohol. Previous studies found that traditionally among African communities, alcohol use was limited to males and to special occasions (128). Alcohol use may be less prominent among females in these regions due to the prevailing traditional cultural norms towards alcohol use among females.…”
Section: Discussionmentioning
confidence: 94%
“…Among those who left school due to the school fees being unaffordable, females residing in the urban areas of KwaZulu Natal and Mpumalanga were less likely to consume high quantities of alcohol, whilst those residing in the rural areas of Gauteng were more likely to consume high quantities of alcohol (Chapter 3). In traditional African communities, alcohol use is usually limited to males and to special occasions (128). The lower alcohol consumption by females in KwaZulu Natal and Mpumalanga may be due to them conforming to prevailing traditional and cultural norms.…”
Section: The Relationship Between Reasons For Leaving School and Alcomentioning
confidence: 99%